COVID-19 in Africa : outcomes and scenarios - Gopaldas, Ronak (2020)
A pandemic has the potential to disproportionately affect Africans. The continent’s healthcare sector is underdeveloped. Its infrastructure is insufficient and its borders are porous. Similarly, the economic fallout for the continent is likely to be severe and enduring. This burden will fall heavily on countries with a high dependence on commodity exports to China, weak sovereign balance sheets, high debt burdens, and volatile currencies, among other external fragilities. In only a few months, rapid spread of the powerful COVID-19 virus rattled global markets and severely hit the world’s growth outlook. The shock disrupted production, trade and global supply chains. African economies, which supply vast resources to China’s manufacturing sector, face a grim outlook. Several African industries already show signs of financial distress. The early victims are mining and tourism, travel and accommodation. African economies are ill prepared to absorb the financial and economic fallout of the pandemic, especially its longer-term implications for growth. This pandemic is generating a series of powerful shocks to the world’s economic, political, and security structures. Its impacts will lead to heightened fear and uncertainty at multiple levels. To understand the likely impacts (short, medium and long-term) of these shocks on the African continent, it is necessary to unpack outcomes at the first (macroeconomic), second (sectoral) and third levels (political and societal).